The Electrochemical Properties of Biochars and How They Affect Soil Redox Properties and Processes - Stephen Joseph; Olivier Husson; Ellen Ruth Graber; Lukas van Zwieten; Sara Taherymoosavi; Torsten Thomas; Shaun Nielsen; Jun Ye; Genxing Pan; Chee Chia; Paul Munroe; Jessica Allen; et al. (Agronomy, 2015)
Biochars are complex heterogeneous materials that consist of mineral phases, amorphous C, graphitic C, and labile organic molecules, many of which can be either electron donors or acceptors when placed in soil. Biochar is a reductant, but its electrical and electrochemical properties are a function of both the temperature of production and the concentration and composition of the various redox active mineral and organic phases present. When biochars are added to soils, they interact with plant roots and root hairs, micro-organisms, soil organic matter, proteins and the nutrient-rich water to form complex organo-mineral-biochar complexes Redox reactions can play an important role in the development of these complexes, and can also result in significant changes in the original C matrix. This paper reviews the redox processes that take place in soil and how they may be affected by the addition of biochar. It reviews the available literature on the redox properties of different biochars. It also reviews how biochar redox properties have been measured and presents new methods and data for determining redox properties of fresh biochars and for biochar/soil systems.